Intersection of Epigenetic and Metabolic Regulation of Histone Modifications in Acute Myeloid Leukemia - Dhall, Abhinav; Zee, Barry M.; Yan, Fangxue; Blanco, M. Andres (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) is one of the most lethal blood cancers, accounting for close to a quarter of a million annual deaths worldwide. Even though genetically heterogeneous, all AMLs are characterized by two interrelated features—blocked differentiation and high proliferative capacity. Despite significant progress in our understanding of the molecular and genetic basis of AML, the treatment of AMLs with chemotherapeutic regimens has remained largely unchanged in the past 30 years. In this review, we will consider the role of two cellular processes, metabolism and epigenetics, in the development and progression of AML and highlight the studies that suggest an interconnection of therapeutic importance between the two. Large-scale whole-exome sequencing of AML patients has revealed the presence of mutations, translocations or duplications in several epigenetic effectors such as DNMT3, MLL, ASXL1, and TET2, often times co-occuring with mutations in metabolic enzymes such as IDH1 and IDH2. These mutations often result in impaired enzymatic activity which leads to an altered epigenetic landscape through dysregulation of chromatin modifications such as DNA methylation, histone acetylation and methylation. We will discuss the role of enzymes that are responsible for establishing these modifications, namely histone acetyl transferases (HAT), histone methyl transferases (HMT), demethylases (KDMs), and deacetylases (HDAC), and also highlight the merits and demerits of using inhibitors that target these enzymes. Furthermore, we will tie in the metabolic regulation of co-factors such as acetyl-CoA, SAM, and α-ketoglutarate that are utilized by these enzymes and examine the role of metabolic inhibitors as a treatment option for AML. In doing so, we hope to stimulate interest in this topic and help generate a rationale for the consideration of the combinatorial use of metabolic and epigenetic inhibitors for the treatment of AML.